The effect of inundation on frog communities and chorusing behaviour. (December 2022) - Sarker, Mohammad Abdur Razzaque; McKnight, Donald T.; Ryder, Darren; Walcott, Amelia; Ocock, Joanne F.; Spencer, Jennifer A.; Preston, David; Brodie, Sheryn; Bower, Deborah S.
Highlights: Wetland inundation from river flow is a major driver structuring frog communities. Environmental water delivery was beneficial for frogs during a drought period. False-colour Spectrogram images were useful in detecting chorusing patterns of frogs. Frogs' chorusing behaviour varied among species and sites in arrival of river flows. Abstract: Globally, river regulation has degraded wetlands, including parts of the Murray-Darling Basin (MDB), an ecologically significant basin in Australia. Frogs in a floodplain environment largely depend on habitats created by river flows, but little is known about how frogs in the northern MDB are impacted by river regulation. We tested how wetland inundation affected frogs in a catchment of the northern MDB. We surveyed frogs between 2015 and 2019 to determine long-term changes in the community composition associated with wetland inundation from river flows. Additionally, we recorded nightly soundscapes for four days before and after the arrival of river flows between 2019 and 2020. The abundance and richness of frog species increased during larger inundation events leading to altered community composition (beta diversity). Warmer temperatures increased frog species richness, and frog community dominance decreased with decreasing vegetation cover (i.e., the relative abundance became more even across species). The abundance of five frog species ( Limnodynastes tasmaniensis, Limnodynastes fletcheri, Crinia parinsignifera, Litoria peronii, and Litoria latopalmata ) was higher in response to increased inundation extent. The total species richness of chorusing frogs increased after the arrival of river flows; six species chorused over the four nights preceding flow, whereas eight species chorused following the flow arrival, but the responses varied among species and sites. Frog species richness increased at three sites after flows, but not at others. After inundation, the choruses of Limnodynastes tasmaniensis increased whereas Limnodynastes fletcheri decreased. Our findings indicate that wetland inundation is beneficial for frog communities and suggest that chorusing behaviour varied in response to river flows inundating floodplain wetlands.